2011
DOI: 10.4103/0972-2327.91950
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of childhood epilepsy in Kerala

Abstract: Background:We aimed to identify the risk factors for epilepsy in children.Materials and Methods:This case–control retrospective study was carried out in the pediatric neurology outpatient service of the Trivandrum Medical College. All children (1–12 years) with epilepsy satisfying the selection criteria were included, after obtaining consent from parents. Those with single seizures or febrile seizures were excluded. Controls were children without epilepsy attending the same hospital. Parents were interviewed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
3
5
0
2
Order By: Relevance
“…There is a non-significant association between the epilepsy and the number of parity (OR= 0.812). This result agrees with the result of Attumalil et al (9), in their study they who found a non-significant relationship between parity and epilepsy. There is a significant association between epilepsy and mother during pregnancy exposure to domestic violence (OR= 2.765).…”
Section: Table (1) Demographic Characteristics Of Study Sample and Th...supporting
confidence: 93%
“…There is a non-significant association between the epilepsy and the number of parity (OR= 0.812). This result agrees with the result of Attumalil et al (9), in their study they who found a non-significant relationship between parity and epilepsy. There is a significant association between epilepsy and mother during pregnancy exposure to domestic violence (OR= 2.765).…”
Section: Table (1) Demographic Characteristics Of Study Sample and Th...supporting
confidence: 93%
“…[ 55 71 ] Perinatal injury, newborn distress, head trauma, neonatal hypoglycemia, malnutrition, and neurocyticersosis were reported as important risk factors of epilepsy in Indian children. [ 89 90 ] Later, majority of studies from India reported a higher prevalence during the 2 nd decade, while a recent estimate from Raina et al ., have reported a higher prevalence in the 4 th decade. [ 24 55 56 59 60 ] This changing pattern in the age-specific occurrence of epilepsy might be linked to demographic transition, changing living conditions, improved healthcare services, changing dietary habits (related to neurocysticercosis (NCC)), increasing awareness, and better help-seeking behaviors.…”
Section: Epidemiological Correlatesmentioning
confidence: 99%
“…Risiko epilepsi pada saudara kandung penderita epilepsi primer kurang lebih 4%. 32 Jika orang tua dan salah satu anaknya samasama menderita epilepsi primer, maka anak yang lain berpotensi 10% terkena epilepsi. 32,33 4.…”
Section: Faktor Risiko Kejang Demam Menjadi Epilepsiunclassified
“…32 Jika orang tua dan salah satu anaknya samasama menderita epilepsi primer, maka anak yang lain berpotensi 10% terkena epilepsi. 32,33 4. Kejang demam sederhana (KDS) berulang 4 episode atau lebih dalam satu tahun.…”
Section: Faktor Risiko Kejang Demam Menjadi Epilepsiunclassified